Trust of Security Systems Among Airport Stakeholders on the Increased Complexity of Security Technology – A Study - Essa Al Falasi, Prof. Madya. Dr. Massila Kamalrudin (International Journal of Advanced Science and Technology, 2020)
The airports as one of the most complex systems in modern society continues to increase in complexity of security control on the increased expansion in global air traffic. The critical role of the airport security systems in preventing the influx of threat has become central to safeguarding citizens and infrastructure against many forms of external attacks. For this reason, airports continue to play a fundamental role in the global socio-economic landscape and modern societies. However, the need to meet all stakeholder security needs, in the course of increasing complexity of operations, have utterly become a challenging endeavour. In this view, trust of security systems by the various stakeholders has become a major cause of concern to airports service quality and performance. In an elaborative case of Dubai International Airport (DXB), the essential socio- economic role of this airport in the UAE, GCC region, and the global aviation industry is rapidly expanding but without clear implications to service quality. The present paper critically analyses the case of DXB using available literature and publicly available data to pave way for future research.